(untitled) - Van Wyk, Robert

The optimization of chilling regimes, carcass weight and electrical inputs to mitigate the risk of high rigor temperature carcasses – a case study (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.